2022
DOI: 10.21037/asj-21-61
|View full text |Cite
|
Sign up to set email alerts
|

Do we even need to relax? Evolution of non-intubated video assisted thoracic surgery thymectomy for myasthenia gravis—a narrative review

Abstract: Objective: Traditional approaches to thymectomy for myasthenia gravis (MG) formerly included open sternotomy and later video-assisted-(VATS) and robot-assisted thoracic surgery (RATS) through traditional double-lumen intubation anaesthesia. The aim of the review was to describe current role of non-intubated (NI) minimally invasive techniques in thoracic surgery with emphasis on NI-VATS thymectomy and point out advantages and disadvantages of the method from both the surgical-and anaesthesiological point of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Liu et al found a 5.88-fold higher incidence of postoperative myasthenic crisis when surgery was performed from thoracotomy versus VATS [139,140]. In addition to the use of thoracic epidural anaesthesia [137], the use of the NITS technique is not associated with the administration of muscle relaxants [141,142]. The use of the NITS technique is limited by several previously published criteria [125][126][127]143].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al found a 5.88-fold higher incidence of postoperative myasthenic crisis when surgery was performed from thoracotomy versus VATS [139,140]. In addition to the use of thoracic epidural anaesthesia [137], the use of the NITS technique is not associated with the administration of muscle relaxants [141,142]. The use of the NITS technique is limited by several previously published criteria [125][126][127]143].…”
Section: Discussionmentioning
confidence: 99%